Membangun Ekosistem Pangan Berkelanjutan: Peran Inovasi Dan E-Commerce di Kabupaten Karawang - Sarman, Rohmat; Juanim, Juanim; Gunardi, Ardi; Aresia Landarica, Bingky; Mustika Sari, Lira (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2026)
his Community Service Program aims to build a sustainable food ecosystem in Karawang Regency through the integration of product innovation and the utilization of e-commerce. The main focus of the activity is to increase the capacity of micro and small business actors in processing black glutinous rice into peuyeum (a typical fermented food) with hygienic production techniques, attractive packaging, and flavor variations according to market trends. In addition, this program provides digital marketing training to expand marketing access through platforms such as social media and e-commerce. The implementation method includes field surveys, product innovation training, technical assistance, and the preparation of practical guidebooks. Survey results show two main challenges: the low added value of local products due to a lack of innovation and limited digital literacy among farmers. The implemented solutions succeeded in improving participants' skills in peuyeum processing and the use of digital marketing technology, with outcomes in the form of increased product competitiveness, market network expansion, and increased business income. Long-term impacts are seen in economic transformation based on collaboration between stakeholders and technology adoption that supports business sustainability Keywords : sustainable food ecosystem, product innovation, e-commerce.